Comparative study of morbidities in sawmills workers from central India: a cross sectional study - Jagtap, Atul Ajay; Deshmukh, Jyotsna (International Journal Of Community Medicine And Public Health, 2018)
Background: The main problem encountered in the sawmill environment is the respirable dust (<10 μm) which may be a cause of respiratory diseases. Further the sawmill workers are also exposed to other health hazards such as injuries from handling wood logs, high noise exposure etc. There are few studies who have studied respiratory health of sawmill workers in India but there is paucity of studies on sawmill workers and their health problems in India. So the study has been undertaken to find out the chief morbidities among sawmill workers by comparing them in control group. Methods: A cross sectional study was conducted among sawmill workers in Nagpur city in central India from September 2013 to December 2015. Information regarding socio-demographic characteristics collected using predesigned proforma by interview technique. Thorough general, systemic examination and anthropometry was done to assess health status. Results: Majority of the study subjects were males and belonged to younger age group (28-37 years). Most common morbidity among sawmill workers was musculoskeletal disorder (Table 4) and it was significantly more than comparison group (p<0.05). Some of the other significantly common morbidities among sawmill workers (p<0.05) were conjunctivitis, rhinitis, injuries, hearing impairment, ARI’s, bronchial asthma, chronic bronchitis, contact dermatitis, abdominal hernia, varicose veins and pulmonary tuberculosis. Conclusions: Musculoskeletal disorders were the commonest morbidity among sawmill workers. Respiratory morbidities and other allergic effects of wood dust were other common morbidities among sawmill workers.